Gonjang-ganjing Turunan Nabi Versus Turunan Wali Songo Sebagai Pendikan Agama Islam Anak Bangsa - nurhidayat nurhidayat; Cecep Sumarna; Didin Nurul Rosidin (Indonesian Journal of Islamic Education, 2023)
There was upheaval between the ulema who were habaib (descendants of Rasulullah) and the ulema who were not habaib. From Habaib's side, there is Habib's excerpt of his lecture, which allegedly insulted scholars who were not habaib and also descendants of the Wali Songo. The scholars who were not habaib denied this and at the same time blamed the habib's statements. This needs to get the attention of educators who will be used as education for their students so that they become adults and continue to strive for their goals in their lives, because both of these parties all have arguments that support their arguments so that it confuses the layman. Differences in opinions are natural, but not for division. Both Habaib, who is a descendant of Ba'alawy and Syarif, who is a descendant of Wali Songo, must all be respected as descendants of the Prophet and as scholars who guide the ummah and defend Indonesia's independence. As for the disputes between them, don't become an obstacle to loving the scholars who teach religion, let them be responsible for themselves to Rasulullah and their God if their confession is wrong. Do not make this dispute, a division and conflict, because the loser is Islam itself.